Positive electrode edge coating adhesive, preparation method of positive electrode edge coating adhesive, positive electrode plate and lithium ion battery
By replacing PVDF with a new non-fluorine binder, combined with polyethylene nitrile rubber, acrylic resin, epoxy silane oligomer and silane coupling agent, the shortcomings of PVDF in terms of flexibility and ductility are solved, significantly improving the flexibility and peel strength of the electrode sheet, and improving the safety and manufacturing efficiency of the battery.
Patent Information
- Application Number
- CN202411737288.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
As a positive electrode edge adhesive, PVDF has shortcomings in flexibility and ductility, which leads to the adhesive layer being easily broken and poses safety risks.
New non-fluorine binders, including polynitrile butadiene rubber, acrylic resin, epoxy silane oligomer and silane coupling agent, are used to replace traditional PVDF, and improve the flexibility and peel strength of the electrode sheet through synergistic effects.
It significantly improves the flexibility and peel strength of the electrode sheet, reduces the risk of rubber layer breakage, improves the safety of the battery, and reduces the manufacturing cost.
Smart Images

Figure CN119529708A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode edge coating adhesive and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] The positive electrode side coating plays a vital role in lithium-ion batteries. It is mainly a binder for boehmite materials, which combines the positive electrode boehmite material and the current collector aluminum foil to form a stable structure. PVDF (polyvinylidene fluoride) is the most commonly used positive electrode side coating material. Due to its excellent chemical stability and corrosion resistance, it can effectively prevent the electrolyte from corroding the electrode material, thereby extending the battery cycle life and improving safety.
[0003] In the production process of lithium-ion batteries, the functions of positive electrode edge coating mainly include: 1. Adhesion: PVDF is commonly used as a binder to ensure the bonding strength between the boehmite material and the current collector during normal charge and discharge of the battery, and prevent the active material from falling off; 2. Stability: PVDF has good electrochemical stability and chemical stability, and can protect the electrode material from being corroded by the electrolyte; 3. Safety: During the use of the battery, PVDF can reduce the risk of internal short circuits caused by expansion or contraction of the material and improve the safety of the battery; 4. Process requirements: During the manufacturing process of the battery, the pole ears need to be welded and folded. The use of PVDF helps to maintain the integrity and electrical insulation of the pole ears in these processes; 5. Environmental adaptability: PVDF's high temperature resistance and low temperature resistance make it suitable for battery applications in various environments.
[0004] However, PVDF as an adhesive for coating the positive electrode side has some deficiencies in flexibility and ductility, which causes the adhesive layer to easily break, posing a safety hazard. Summary of the invention
[0005] In order to solve the problem of poor flexibility and ductility of PVDF when used as an adhesive for coating the positive electrode edge in the prior art, the present invention adopts a new non-fluorine binder to replace traditional PVDF, and balances the performance in comprehensively improving the flexibility of the electrode sheet, improving the peeling strength with the current collector and the electrolyte resistance. At the same time, it can improve the NMP baking energy efficiency during the processing process, improve the cross-linking phenomenon between the processing and coating process and the positive electrode slurry, and at the same time achieve the performance advantages of high solid thick coating.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A positive electrode edge coating adhesive, the raw materials include the following components in parts by weight: 15-19 parts of solution polymerized nitrile rubber; 1-3 parts of acrylic resin; 0.1-3 parts of epoxy silane oligomer; Silane coupling agent 0.1-5 parts; 70-85 parts of N-methylpyrrolidone.
[0007] Optionally, the mass content of acrylonitrile in the solution-polymerized nitrile rubber is 20%-45%.
[0008] Optionally, the degree of hydrogenation of the solution-polymerized nitrile rubber is 20% to 80%.
[0009] Optionally, the acrylic resin is a thermoplastic acrylic resin.
[0010] Optionally, the acrylic resin is selected from at least one of Hanwha S60L, Rohm and Haas B44, and Mitsubishi MB-2600.
[0011] Optionally, the silane coupling agent is selected from at least one of KH-550, KH-560, KH-570, KH-151, KH-171, KH-580, KH-602, and KH-792.
[0012] Another object of the present invention is to provide a method for preparing the positive electrode edge coating adhesive as described above, comprising the following steps: S1: According to the formula, acrylic resin, N-methylpyrrolidone A, epoxy silane oligomer A, and silane coupling agent A are mixed to obtain solution A; S2: According to the formula, the solution-polymerized nitrile rubber, N-methylpyrrolidone B, epoxy silane oligomer B, and silane coupling agent B are mixed to obtain a solution B; S3: According to the formula, the solution A, the solution B and N-methylpyrrolidone C are added to the stirring kettle in sequence, the temperature is controlled not higher than 40° C. After stirring and dissolving, filtering and packaging are performed to obtain the positive electrode edge coating adhesive.
[0013] Another object of the present invention is to provide a positive electrode sheet, comprising the positive electrode edge-coated adhesive as described above.
[0014] Another object of the present invention is to provide a lithium-ion battery, comprising the positive electrode sheet as described above.
[0015] The beneficial effects of the present invention are: The positive electrode edge coating adhesive provided by the present invention adopts a new type of non-fluorine binder to replace the traditional PVDF, and introduces solution-polymerized nitrile rubber to cooperate with acrylic resin, epoxy silane oligomer and silane coupling agent to achieve a balance in performance in comprehensively improving the flexibility of the pole piece, improving the peeling strength with the current collector and the electrolyte resistance, and at the same time can improve the N-methylpyrrolidone (NMP) baking energy efficiency during the processing process, improve the cross-linking phenomenon with the positive electrode slurry during the processing and coating process, and at the same time achieve the performance advantage of high solid thick coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0017] Figure 1 This is a picture of the slurry and the LFP positive electrode slurry dripping on each other for 3 minutes in Example 1 of the present invention; Figure 2 This is a picture taken after PVDF slurry and LFP positive electrode slurry were dripped on each other for 3 minutes. DETAILED DESCRIPTION
[0018] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0019] When PVDF is used as an adhesive for coating the positive electrode, in addition to its poor flexibility and ductility, its crystallinity is generally around 50%, and its crystalline melting temperature is around 140°C. Therefore, at the normal operating temperature of the battery, the crystallinity of PVDF makes it difficult for molecules in the electrolyte to circulate. When preparing the battery, if the drying speed is not appropriate, the shrinkage rate of PVDF and the current collector will differ greatly, and boehmite substances will fall off from the current collector. Even if there is no problem after coating and drying, as time passes, during use, the electrode adhesive layer will be partially or completely peeled off from the current collector due to the internal stress of the electrode, causing safety hazards. In addition, the market price of PVDF is high, which will increase the cost of the battery manufacturing process.
[0020] Based on this, in order to solve the problem of poor flexibility and ductility of PVDF as a positive electrode edge coating adhesive in the prior art, the present invention provides a positive electrode edge coating adhesive, and its raw materials include the following components in parts by weight: 15-19 parts of solution polymerized nitrile rubber; 1-3 parts of acrylic resin; 0.1-3 parts of epoxy silane oligomer; Silane coupling agent 0.1-5 parts; 70-85 parts of N-methylpyrrolidone.
[0021] The positive electrode edge coating adhesive provided by the present invention adopts a new type of non-fluorine binder to replace the traditional PVDF, and introduces solution-polymerized nitrile rubber to cooperate with acrylic resin, epoxy silane oligomer and silane coupling agent to achieve a balance in performance in comprehensively improving the flexibility of the pole piece, improving the peeling strength with the current collector and the electrolyte resistance, and at the same time can improve the N-methylpyrrolidone (NMP) baking energy efficiency during the processing, improve the cross-linking phenomenon with the positive electrode slurry, and achieve the performance advantage of high solid thick coating.
[0022] In the positive electrode side coating adhesive provided by the present invention, the weight ratio of polynitrile rubber to acrylic resin is preferably (15-19): (1-3), and the weight ratio of polynitrile rubber to acrylic resin is further preferably 18:2, so as to avoid excessive acrylic resin content, which may cause poor electrolyte resistance; or due to too little acrylic resin content, the dispersion ability of boehmite will be slightly poor, which is not conducive to slurry processing.
[0023] The present invention further preferably has an acrylonitrile mass content of 20%-40% and a butadiene content of 60%-80% in the solution-polymerized nitrile rubber. By controlling a certain acrylonitrile segment content, it can be ensured that the binder has both certain strength and excellent flexibility; so as to avoid the film performance being too hard due to the acrylonitrile mass content in the solution-polymerized nitrile rubber being too high, or the strength being too low due to the acrylonitrile content being too low, resulting in low electrolyte resistance and electrode cohesive strength, which affects normal use.
[0024] Furthermore, the present invention preferably has a hydrogenation degree of 25% to 85% for the solution-polymerized nitrile rubber, so as to avoid poor solvent resistance when the hydrogenation degree of the solution-polymerized nitrile rubber is greater than 85%, and a higher degree of crosslinking is required when the hydrogenation degree is less than 25%, resulting in flexibility deviation.
[0025] Specifically, the preferred solution polymerized nitrile rubber in the present invention is ARLANXEO Therban 3496.
[0026] The structure of the solution-polymerized nitrile rubber is mainly linear and straight chain, which can ensure the effective dissolution of the binder in the solvent N-methylpyrrolidone (NMP) on the one hand, and obtain a more appropriate viscosity on the other hand, which is helpful for the processing of the subsequent slurry.
[0027] The present invention mainly solves the technical problem of poor flexibility of PVDF. The final product prepared by the scheme provided by the present invention has an elongation at break that is more than 3 times that of PVDF. At the same time, the peeling strength between the scheme and the current collector is more than 2 times that of PVDF, which greatly improves the detachment problem of PVDF in long-term application of battery edge coating.
[0028] In order to take into account the bonding performance and flexibility of the positive electrode edge coating adhesive, the present invention preferably uses a thermoplastic acrylic resin as the acrylic resin, and further preferably uses the acrylic resin selected from at least one of Hanwha S60L, Rohm and Haas B44, and Mitsubishi MB-2600; the epoxy silane polymer is preferably selected from at least one of Guangzhou Longkai Chemical LK-168 / LK-560 / LK-5060 / LK-636, American Momentive MP-200, Evonik 2926, and Runda LD-3138; the epoxy silane polymer can undergo a high-temperature cross-linking reaction with the double bonds of butadiene and the carboxyl groups of the acrylic resin, and has good compatibility with NMP, and will not affect the storage stability of the adhesive at room temperature.
[0029] In the present invention, the preferred silane coupling agent is at least one selected from KH-550, KH-560, KH-570, KH-151, KH-171, KH-580, KH-602, and KH-792.
[0030] The present invention preferably uses a mass ratio of epoxy silane polymer to silane coupling agent of 1:4 to prevent excessive addition of epoxy silane polymer, which may lead to excessive improvement of mechanical strength, thereby weakening flexibility and decreasing peel strength; or insufficient solvent resistance due to too low addition of epoxy silane polymer; in addition, increasing the addition of silane coupling agent does not improve solvent resistance as significantly as adding epoxy silane polymer, and reducing the addition of silane coupling agent has a greater impact on the peel strength with the substrate.
[0031] The positive electrode edge coating adhesive provided by the present invention can ensure good flexibility of the insulating layer and reduce curling and powder loss in actual positive electrode edge coating applications; the prepared adhesive film has a low dissolution rate and good solvent resistance; and the positive electrode edge coating adhesive provided by the present invention does not contain fluorine in the formula system, so it has certain advantages in fluorine-free environmental protection.
[0032] Another object of the present invention is to provide a method for preparing the positive electrode edge coating adhesive as described above, the preparation method comprising the following steps: S1: According to the formula, acrylic resin, N-methylpyrrolidone A, epoxy silane oligomer A, and silane coupling agent A are mixed to obtain solution A; S2: According to the formula, the solution-polymerized nitrile rubber, N-methylpyrrolidone B, epoxy silane oligomer B, and silane coupling agent B are mixed to obtain a solution B; S3: According to the formula, add solution A, solution B, and N-methylpyrrolidone C to the stirring kettle in sequence, control the temperature not higher than 40°C, stir and dissolve, filter and package, preferably 200 mesh filtration and packaging, to obtain the positive electrode edge coating adhesive.
[0033] It should be noted that the N-methylpyrrolidone component in steps S1-S3 is the same. Since the amount of N-methylpyrrolidone used in each step is different, for the convenience of distinction, the N-methylpyrrolidone in S1-S3 is respectively recorded as N-methylpyrrolidone A, N-methylpyrrolidone B, and N-methylpyrrolidone C; and, in step S3, whether NMP needs to be added and the amount of addition are determined based on the solid content and viscosity.
[0034] In order to ensure the performance of the adhesive coated on the positive electrode side, the present invention preferably requires that the materials in the above steps, such as solution-polymerized nitrile rubber and acrylic resin powder, are vacuum-baked at 90°C to remove water before use, and the moisture content shall not exceed 1500 ppm. All mixing and stirring kettles need to be vacuum-evacuated to remove water before use.
[0035] Another object of the present invention is to provide a positive electrode sheet, which includes the positive electrode edge-coated adhesive as described above.
[0036] The positive electrode sheet provided by the present invention uses a new type of non-fluorine-based adhesive to replace traditional PVDF as the positive electrode edge coating adhesive. By introducing solution-polymerized nitrile rubber, it works synergistically with acrylic resin, epoxy silane oligomer and silane coupling agent to achieve a balance in performance in terms of comprehensively improving the flexibility of the electrode sheet, improving the peeling strength with the current collector and electrolyte resistance, and at the same time can improve the N-methylpyrrolidone (NMP) baking energy efficiency during the processing process, thereby achieving the performance advantage of high solid thick coating.
[0037] Another object of the present invention is to provide a lithium ion battery, which includes the positive electrode sheet as described above.
[0038] The lithium-ion battery provided by the present invention has a positive electrode edge coating adhesive in a positive electrode sheet, and adopts a novel non-fluorine-based binder to replace the traditional PVDF. By introducing solution-polymerized nitrile rubber, it cooperates with acrylic resin, epoxy silane oligomer and silane coupling agent to achieve a balance in performance in terms of comprehensively improving the flexibility of the electrode sheet, improving the peeling strength with the current collector and electrolyte resistance, and can also improve the N-methylpyrrolidone (NMP) baking energy efficiency during the processing, thereby achieving the performance advantage of high solid thick coating.
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0040] Unless otherwise specified, the solution polymerized nitrile rubber in the embodiments and comparative examples of the present invention is Arlanxeo Therban 3496, the acrylic resin is Hanwha S60L, the epoxy silane oligomer is Momentive MP-200, and the silane coupling agent is KH-550.
[0041] Example 1 This embodiment provides a method for preparing a positive electrode edge coating adhesive, the preparation method comprising the following steps: S1: 20 parts by weight of acrylic resin, 75 parts by weight of N-methylpyrrolidone A, 1 part by weight of epoxy silane oligomer A, and 4 parts by weight of silane coupling agent A are mixed to prepare an NMP solution of acrylic resin to obtain solution A; S2: 20 parts by weight of solution-polymerized nitrile rubber, 75 parts by weight of N-methylpyrrolidone B, 1 part by weight of epoxysilane oligomer B, and 4 parts by weight of silane coupling agent B are mixed to prepare an NMP solution of solution-polymerized nitrile rubber to obtain solution B; S3: Add 10 parts by weight of solution A and 90 parts by weight of solution B to a stirring kettle in sequence, control the temperature not higher than 40° C., stir and dissolve evenly, filter and package through 200 mesh to obtain a positive electrode side-coated adhesive.
[0042] Example 2 This embodiment provides a method for preparing a positive electrode edge coating adhesive, the preparation method comprising the following steps: S1: 20 parts by weight of acrylic resin, 75 parts by weight of N-methylpyrrolidone A, 1 part by weight of epoxy silane oligomer A, and 4 parts by weight of silane coupling agent A are mixed to prepare an NMP solution of acrylic resin to obtain solution A; S2: 20 parts by weight of solution-polymerized nitrile rubber, 75 parts by weight of N-methylpyrrolidone B, 1 part by weight of epoxysilane oligomer B, and 4 parts by weight of silane coupling agent B are mixed to prepare an NMP solution of solution-polymerized nitrile rubber to obtain solution B; S3: Add 15 parts by weight of solution A and 85 parts by weight of solution B to a stirring kettle in sequence, control the temperature to be no higher than 40° C., stir and dissolve evenly, filter and package through 200 mesh to obtain a positive electrode side-coated adhesive.
[0043] Example 3 This embodiment provides a method for preparing a positive electrode edge coating adhesive, the preparation method comprising the following steps: S1: 20 parts by weight of acrylic resin, 75 parts by weight of N-methylpyrrolidone A, 1 part by weight of epoxy silane oligomer A, and 4 parts by weight of silane coupling agent A are mixed to prepare an NMP solution of acrylic resin to obtain solution A; S2: 20 parts by weight of solution-polymerized nitrile rubber, 75 parts by weight of N-methylpyrrolidone B, 1 part by weight of epoxysilane oligomer B, and 4 parts by weight of silane coupling agent B are mixed to prepare an NMP solution of solution-polymerized nitrile rubber to obtain solution B; S3: Add 5 parts by weight of solution A and 95 parts by weight of solution B to a stirring kettle in sequence, control the temperature not higher than 40° C., stir and dissolve evenly, filter and package through 200 mesh to obtain a positive electrode side-coated adhesive.
[0044] Each comparative example of the present invention is used for comparison with Example 1.
[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that the solution polymerized nitrile rubber is ARLANXEO Therban 4498, and its acrylonitrile content is 44%.
[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that the solution polymerized nitrile rubber is ARLANXEO Therban LT 1707, and its acrylonitrile content is 17%.
[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that the solution-polymerized nitrile rubber is Perbunan 3445 produced by BAYER of Germany, and its degree of hydrogenation is 0.
[0048] Comparative Example 4 The difference between this comparative example and Example 1 is that the solution-polymerized nitrile rubber is ARLANXEO Therban LT 2007, and its MER hydrogenation degree is 99.1%.
[0049] Comparative Example 5 This comparative example provides a method for preparing a positive electrode edge coating adhesive, the preparation method comprising the following steps: S1: 20 parts by weight of acrylic resin, 75 parts by weight of N-methylpyrrolidone A, 1 part by weight of epoxy silane oligomer A, and 4 parts by weight of silane coupling agent A are mixed to prepare an NMP solution of acrylic resin to obtain solution A; S2: 20 parts by weight of solution-polymerized nitrile rubber, 75 parts by weight of N-methylpyrrolidone B, 1 part by weight of epoxysilane oligomer B, and 4 parts by weight of silane coupling agent B are mixed to prepare an NMP solution of solution-polymerized nitrile rubber to obtain solution B; S3: Add 30 parts by weight of solution A and 70 parts by weight of solution B to a stirring kettle in sequence, control the temperature to be no higher than 40° C., stir and dissolve evenly, filter and package through 200 mesh to obtain a positive electrode side-coated adhesive.
[0050] Comparative Example 6 This comparative example provides a method for preparing a positive electrode edge coating adhesive, the preparation method comprising the following steps: S1: 20 parts by weight of acrylic resin, 75 parts by weight of N-methylpyrrolidone A, 1 part by weight of epoxy silane oligomer A, and 4 parts by weight of silane coupling agent A are mixed to prepare an NMP solution of acrylic resin to obtain solution A; S2: 20 parts by weight of solution-polymerized nitrile rubber, 75 parts by weight of N-methylpyrrolidone B, 1 part by weight of epoxysilane oligomer B, and 4 parts by weight of silane coupling agent B are mixed to prepare an NMP solution of solution-polymerized nitrile rubber to obtain solution B; S3: Add 2 parts by weight of solution A and 98 parts by weight of solution B to a stirring kettle in sequence, control the temperature to be no higher than 40°C, stir and dissolve evenly, filter and package through 200 mesh to obtain a positive electrode side-coated adhesive.
[0051] Performance Test: 1. Film performance test The positive electrode side coating adhesive and polyvinylidene fluoride (PVDF) HSV-900 provided in each embodiment and comparative example are respectively prepared into NMP solutions, and a film is prepared in a polytetrafluoroethylene mold, wherein: The preparation method of the PVDF film is as follows: S01, prepare 8% solid content PVDF NMP solution; S02. Weigh 75 g of the above solution into a 10x10 cm polytetrafluoroethylene mold, bake it in a 60°C forced air oven for 4 h, then raise the temperature to 110°C and continue baking for 12 h to obtain the prepared adhesive film.
[0052] The preparation methods of the films of the embodiments and comparative examples are as follows: 24 g of the positive electrode side coating adhesive prepared in each embodiment and comparative example was weighed into a 10×10 cm polytetrafluoroethylene mold, baked in a 60° C. forced air oven for 4 h, and then heated to 110° C. and baked for 12 h to obtain a prepared adhesive film.
[0053] 1. Flexibility test After punching each film into a dumbbell-shaped strip with a width of 4 mm using a punching machine, the tensile curve of the strip was tested. The test results are shown in Table 1.
[0054] 2. Solvent resistance test The prepared films were immersed in a polar mixed solvent of EC / PC / DMC / PP=2 / 2 / 3 / 3 and a lithium salt electrolyte containing 1M LiPF6 EC:EMC:DMC=1:1:1, respectively. After immersion at 60°C for three days, the weight gain (i.e., swelling rate) of the films was tested, and the mass completely dissolved in the mixed solvent (i.e., dissolution rate) was measured by baking at a high temperature of 150°C. The test results are shown in Table 1.
[0055] It can be clearly found from the data in Table 1 that the elongation at break of the adhesive film of each embodiment is significantly higher than that of the PVDF adhesive film, and the tensile strength is significantly lower than that of the PVDF adhesive film, indicating that the adhesive prepared in each embodiment can ensure good flexibility of the insulating layer and reduce the curling and powdering in the actual positive electrode edge coating application; at the same time, it can be found that with the increase in the weight fraction of the silane coupling agent and the epoxy silane oligomer in the system, the dissolution rate of the adhesive film can be greatly reduced, and the epoxy silane oligomer can react with the double bond of butadiene / the carboxyl group of acrylic acid to cross-link. By adjusting the introduction ratio of the silane coupling agent and the epoxy silane oligomer, the cross-linking degree of the adhesive can be appropriately improved, giving it a certain mechanical strength, heat resistance and chemical resistance, while having little effect on flexibility. This method can organically bond inorganic materials such as metal substrate aluminum foil, fillers and organic polymers such as thermoplastic / thermosetting elastomers together, thereby playing a role in improving adhesion. According to the addition ratio in the above embodiment, the dissolution rate is basically close to that of PVDF, ensuring its good solvent resistance.
[0056] 2. Testing of ceramic edge coating slurry performance The adhesives prepared in the examples and comparative examples and PVDF were respectively used to prepare ceramic edge coating slurries according to the following formulas: Taking the solid content of the adhesive as 25% as a benchmark, the adhesive, boehmite (particle size range 0.3~10μm) and NMP were added into a dispersion tank for stirring and dispersion to prepare a ceramic slurry, wherein the weight proportions of the adhesive, boehmite and NMP were 80 / 80 / 21.8 respectively.
[0057] 1. Slurry dispersion and solid content During the slurry preparation process, it was found that under the same homogenization time, the slurry fineness of each embodiment was better. When the ceramic edge coating slurry was coated on the aluminum foil current collector, the surface was relatively smooth and there were no obvious particles. This was mainly attributed to the specific acrylic resin selected in the embodiment formula. The residual carboxylic acid group can have a certain dispersion of the filler. In addition, it was found that the embodiment can make a slurry with a higher solid content. Through exploration, the embodiment can achieve a solid content of >50%, which can simultaneously meet the thick coating in practical applications. PVDF has a larger molecular weight and its own thixotropy and viscosity. The solid content of the slurry that can be prepared under the same formula viscosity is about 25%-30%. The lower solid content makes thick coating more difficult. In addition, the advantage of the high solid content of the embodiment slurry can also greatly reduce the baking energy efficiency of NMP volatilization during construction, and it is more environmentally friendly.
[0058] 2. Peel strength The ceramic slurries made from the above embodiment and PVDF are coated on aluminum foil to make pole pieces, with a coating thickness of 50-70 μm and a surface density of 50-70 g / m 2After rolling, the peel strength was measured according to the 180° peel strength test method, and the test results are shown in Table 1. From the test results, it is found that the peel strength of each embodiment is 2.5 times that of PVDF, indicating that the adhesive prepared in the embodiment has a significant advantage in peel strength.
[0059] 3. Test of cross-linking performance with positive electrode slurry Preparation of LFP cathode slurry: According to the formula PVDF:SP:LFP=2:1:97, the cathode slurry was prepared with solvent NMP, and the solid content was 60%; Preparation of PVDF ceramic slurry: According to the formula of PVDF: boehmite = 2:8, the ceramic slurry was prepared with solvent NMP, with a solid content of 30%; The ceramic edge coating slurry and PVDF ceramic slurry prepared in each embodiment and comparative example were respectively dripped with the above-mentioned LFP positive electrode slurry on aluminum foil. The specific results are shown in Table 1. The picture of the slurry of Example 1 and the LFP positive electrode slurry dripped for 3 minutes is shown in Figure 1, and the picture of the PVDF slurry and the LFP positive electrode slurry dripped for 3 minutes is shown in Figure 2. Figure 2 As shown in the accompanying drawings, it can be seen that no cross-linking phenomenon was found in the ceramic slurry of Example 1 for about 3 minutes, and the interface was relatively clear, while cross-linking occurred at the interface of the PVDF positive electrode slurry of the comparison group.
[0060] Table 1 Note: Electrolyte formula: (1M LiPF6 EC:EMC:DMC=1:1:1) Test swelling rate Electrolyte formula: EC:PC:PP:DMC=2:2:3:3, test dissolution rate It can be seen from the data in Table 1 that, compared with traditional PVDF, the adhesive prepared in each embodiment of the present invention has achieved a balance in performance in comprehensively improving the flexibility of the electrode, improving the peeling strength with the current collector and the electrolyte resistance, and at the same time can improve the NMP baking energy efficiency during the processing process, and achieve the performance advantage of high solid thick coating.
[0061] The mass content of acrylonitrile in the solution-polymerized nitrile rubber of Comparative Example 1 is higher than 40%, resulting in that the performance of the film prepared by the positive electrode edge coating adhesive provided in Comparative Example 1 is relatively hard, and the flexibility of the electrode is not sufficiently improved during the processing; the mass content of acrylonitrile in the solution-polymerized nitrile rubber of Comparative Example 2 is lower than 20%, resulting in that the strength of the positive electrode edge coating adhesive provided in Comparative Example 2 is very low, resulting in low electrolyte resistance and electrode cohesive strength, and the electrode has a risk of demolding after immersion and cannot be used normally.
[0062] The degree of hydrogenation of the solution-polymerized nitrile rubber in Comparative Example 3 is lower than 25%. Although it can be well dissolved in NMP, there is a large room for improvement in cross-linking, and it is difficult to reasonably improve it through the silane coupling agent and epoxy silane polymer in the later stage. Once the over-crosslinking is insufficient, the electrolyte resistance is poor, and the excessive cross-linking leads to poor flexibility. The degree of hydrogenation of the solution-polymerized nitrile rubber in Comparative Example 4 is greater than 85%, the residual double bond content is insufficient, and the room for improvement in post-crosslinking is limited, resulting in a decrease in electrolyte resistance and inability to use normally.
[0063] In Comparative Example 5, the acrylic resin content is too much, which has excess dispersibility for boehmite, and because the molecular weight of this type of acrylic resin is not high, it will cause the electrolyte resistance to deteriorate; in Comparative Example 6, the acrylic resin content is too little, and the dispersibility for boehmite will be slightly poor, which is not conducive to slurry processing and will also cause slight cross-linking.
[0064] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A positive electrode side coating adhesive, characterized in that: The raw materials include the following components in parts by weight: 15-19 parts of solution polymerized nitrile rubber; 1-3 parts of acrylic resin; 0.1-3 parts of epoxy silane oligomer; Silane coupling agent 0.1-5 parts; 70-85 parts of N-methylpyrrolidone.
2. The positive electrode edge coating adhesive according to claim 1, characterized in that: The mass content of acrylonitrile in the solution polymerized nitrile rubber is 20%-45%.
3. The positive electrode edge coating adhesive according to claim 1, characterized in that: The degree of hydrogenation of the solution polymerized nitrile rubber is 25% to 85%.
4. The positive electrode edge coating adhesive according to claim 1, characterized in that: The acrylic resin is a thermoplastic acrylic resin.
5. The positive electrode edge coating adhesive according to claim 4, characterized in that: The acrylic resin is selected from at least one of Hanwha S60L, Rohm and Haas B44, and Mitsubishi MB-2600.
6. The positive electrode edge coating adhesive according to claim 1, characterized in that: The silane coupling agent is selected from at least one of KH-550, KH-560, KH-570, KH-151, KH-171, KH-580, KH-602, and KH-792.
7. A method for preparing a positive electrode edge coating adhesive as claimed in any one of claims 1 to 6, characterized in that: The steps include: S1: According to the formula, acrylic resin, N-methylpyrrolidone A, epoxy silane oligomer A, and silane coupling agent A are mixed to obtain solution A; S2: According to the formula, the solution-polymerized nitrile rubber, N-methylpyrrolidone B, epoxy silane oligomer B, and silane coupling agent B are mixed to obtain a solution B; S3: According to the formula, the solution A, the solution B and N-methylpyrrolidone C are added to the stirring kettle in sequence, the temperature is controlled not higher than 40° C. After stirring and dissolving, filtering and packaging are performed to obtain the positive electrode edge coating adhesive.
8. A positive electrode sheet, characterized in that: It comprises the positive electrode edge coating adhesive as described in any one of claims 1 to 6.
9. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 8.